Evaluation of the levels of stress in the elderly living at home - Juliana Ladeira Garbaccio; Alanna Gomes da Silva; Morgana Michella Barbosa (Universidade Federal do Ceará, 2014)
This study aimed at evaluating the stress level of the elderly assisted by the Primary Health Care of Piumhi, in the Midwest of Minas Gerais, Brazil, in 2010. This was a cross-sectional research with of 64 elderly residents in households. There was a predominance of older women. Regarding chronic diseases 81.3% were bearers of chronic diseases, 75% were cardiac and 29.7% had depression. In the Inventory of Symptoms of Stress for Adults, seniors kept the average 7 (low stress), being more frequent cognitive stress. Female gender was associated with stress level (p<0.05). The elderly showed a good physical and mental status, and we identified low levels of stress, predominantly the cognitive stress type.